Update on Melasma-Part II: Treatment - Cassiano, Daniel P.; Esposito, Ana Claudia C. [UNESP]; Silva, Carolina N. da [UNESP]; Lima, Paula B. [UNESP]; Dias, Joana A. F.; Hassun, Karime; Miot, Luciane D. B.; Miot, Helio A. [UNESP]; Bagatin, Edileia (Adis Int Ltd, 2022)
Melasma is a prevalent chronic relapsing pigmentary disorder that affects photoexposed areas, especially in women of childbearing age. Although there is currently no curative treatment available for melasma, this manuscript critically reviews the knowledge regarding photoprotection, topical and oral therapies, and procedures such as peelings, laser, and microneedling that represent the main strategies for control and prevention of this disease. As the pathogenesis of melasma is not entirely understood, there are prospects for the development of new therapeutic strategies that might act on the pathways that promote sustained pigmentation rather than merely decreasing melanin synthesis and removing melanin from the epidermis.
Keywords: Melasma; Peeling; Sunscreen; UV radiation; Laser